A study on buying behaviour of employers for group life and health insurances in Turkey - İpek, Deniz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1990., 1990)
In this thesis, the buying behaviour of employers for group life and health insurances in Turkey, the factors affecting buying behaviour and order of importances for employers, the employers' preferences in choosing their insurance companies ( whether local or multinational ), additional coverages they would like to have and the problems associated with the current group insurance products/companies have been investigated. The research is exploratory in nature and extensive preliminary work has been done on the subject matter. The employers who have purchased group life and/or health insurance formed the sample of the study. In general, it is found out that employers consider themselves as socially obliged to make the employees feel secure. This is the most important reason for purchasing this employee benefit because of lack of nationwide social welfare programs in Turkey and Social Insurance InstitutionsJs insufficient medical services. The study includes literature review and the field study which is conducted through a questionnaire. The interpretation of data is conducted through computer analysis and implications for insurance companies are presented.
Keywords: Insurance, Group.; Insurance, Life.; Insurance, Health.